The Effect of Profitability, Sales Growth, and Firm Size on Corporate Social Responsibility Disclosure - Yausi Rara Putri (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2020)
Corporate Social Responsibility disclosure is an information that contains social responsibility activities carried out by the company towards social environment. The preparation of Corporate Social Responsibility disclosure using the GRI Standards and the result is a Sustainability report. This research aims to analyze the effect of profitability, sales growth, and firm size on Corporate Social Responsibility disclosure in Index Kompas100 companies listed in IDX 2017-2018. The sample in this research amounted to 17 companies in tne Kompas100 index 2017-2018. The research method is quantitative and is processed using Eviews 10 software. The results of profitability, sales growth, and firm size simultaneously have a significant effect on Corporate Social Responsibility. Partially, only firm size has a positive significant effect on Corporate Social Responsibility disclosure